2008
DOI: 10.1186/1475-2859-7-22
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of biologically active interferon-gamma inducible protein-10 (IP-10) by Lactococcus lactis

Abstract: Background: Chemokines are a large group of chemotactic cytokines that regulate and direct migration of leukocytes, activate inflammatory responses, and are involved in many other functions including regulation of tumor development. Interferon-gamma inducible-protein-10 (IP-10) is a member of the C-X-C subfamily of the chemokine family of cytokines. IP-10 specifically chemoattracts activated T lymphocytes, monocytes, and NK cells. IP-10 has been described also as a modulator of other antitumor cytokines. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Moreover, Lactococcus lactis has been widely used for recombinant therapeutic proteins production, therapeutic drug delivery and vaccine production. [16][17][18][19][20] L. lactis was grown overnight at 30 ºC in M17 medium supplemented with 0.5% glucose in static conditions. After adding the grown culture over the material surface at 30 ° C, we observed that L. lactis adhered, colonized and formed a cocontinuous, stable bacteria multilayer on different material surfaces (polymers, glass, etc.)…”
Section: Functional Living Biointerphasesmentioning
confidence: 99%
“…Moreover, Lactococcus lactis has been widely used for recombinant therapeutic proteins production, therapeutic drug delivery and vaccine production. [16][17][18][19][20] L. lactis was grown overnight at 30 ºC in M17 medium supplemented with 0.5% glucose in static conditions. After adding the grown culture over the material surface at 30 ° C, we observed that L. lactis adhered, colonized and formed a cocontinuous, stable bacteria multilayer on different material surfaces (polymers, glass, etc.)…”
Section: Functional Living Biointerphasesmentioning
confidence: 99%
“…The use of lactococci as cell factories for the production of bacterial and viral antigens has been achieved by Villatoro-Hernandez et al (2008) and Bahey-El-Din et al (2008). For the development of oral vaccines against PCV2 disease, L. lactis NZ9000, one of the most widely used hosts, was used as a delivery vehicle in the production of Cap protein and its derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…Protein extraction and sample preparation from L. lactis, SDS-PAGE and Western Blotting were performed as previously reported (Villatoro-Hernandez et al 2008).…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…We have previously demonstrated that one strain of L. lactis genetically engineered to express human chemokine lymphotactin (LTN) is able to secrete at least 500 ng per ml of culture in 1 h (Zavala-Flores et al 2009). We also demonstrated that human interferon-gamma inducible protein-10 (IP-10) from a different strain of L. lactis genetically manipulated to express and secrete this human chemokine is able to chemo-attract human T lymphocytes (Villatoro-Hernandez et al 2008). This chemokine has been the focus of many studies due to its antitumoral activity in different types of tumor cells (Frederick and Clayman 2001).…”
Section: Introductionmentioning
confidence: 96%